Konsep I'rab Dalam Pandangan Ibrahim Musthafa dan Ibrahim Anis - Hazuar, Hazuar (Arabiyatuna : Jurnal Bahasa Arab, 2019)
There are some objectives on discussion of I?rab concept in Ibrahim Mustafa and Ibrahim Anis perspectives. The mehod used in this research was Descriptive Analysis. In his book, Ihya? al-Nahwi Ibrahim Mustafa explains that there are only two I?rab; Dhammah and Kasrah. Dhammah functions as subject (Isnad), meanwhile Kasrah functions as majmu? ( idhafah). He rejected fathah as i?rab because it is only lines which is seldom communicated by Arabians, and it doesnt infuence meaning for communication. On the contrary, i?rab concept as stated by Ibrahim Anis who declined that there were funtions of i?rab neither rules nor meaning. The findings of this reserch that i?rab concept stated by Ibrahim Mustafa and Ibrahim Anis was contrast. I?rab concept used by Ibrahim is simillar to Ibnu Mada? al-Qurtubi on which the changing of i?rab was caused of ?amil (actor) as it was used by experts of Nahwu traditionally. However, i?rab concept used by Ibrahim Anis rather the same as the thoughts of Nahwu Qutrub which is extremely used i?rab in ditermining a meaning. Then Ibrahim Anis view that the function of i?rab was result the experts of Nahwu.